1982
DOI: 10.1097/00004032-198201000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic Effects of Radon Daughters, Uranium Ore Dust and Cigarette Smoke in Beagle Dogs

Abstract: The development of pulmonary lesions in beagle dogs was studied following chronic inhalation exposures to radon (at 105 % 20 nCi/l), radon daughters (at 605 k 169 WL), uranium ore dust (at 12.9 5 6.7 mglm') and cigarette smoke. Chronic exposures to mixtures of these agents caused significant lifespan shortening when compared with controls. Survival times of controls and smoke-exposed dogs were equivalent during the 4 to 5-yr mean survival time of the dogs exposed to radon-daughter and ore-dust mixtures (with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 5 publications
(6 reference statements)
0
23
0
Order By: Relevance
“…Studies of miners in mines other than uranium have also demonstrated the role of radon in bronchogenic cancer (Lubin et al, 1990;Radford & St. Clair Renard 1984;Morrison et al, 1988). The results of these epidemiological studies and of certain animal studies (Cross et al, 1982;Chameaud et al, 1985) led the International Agency for Research on Cancer (IARC) in 1987 to include radon in the list of carcinogenic substances in humans (IARC vol. 43).…”
mentioning
confidence: 99%
“…Studies of miners in mines other than uranium have also demonstrated the role of radon in bronchogenic cancer (Lubin et al, 1990;Radford & St. Clair Renard 1984;Morrison et al, 1988). The results of these epidemiological studies and of certain animal studies (Cross et al, 1982;Chameaud et al, 1985) led the International Agency for Research on Cancer (IARC) in 1987 to include radon in the list of carcinogenic substances in humans (IARC vol. 43).…”
mentioning
confidence: 99%
“…After habituation dogs tolerated as many as 20 cigarettes in an 8 hour period. This equipment was employed by CROSS et al (385) in a study, which examined the effect of chronic cigarette smoke exposure on pulmonary lesions in beagle dogs. An ancillary observation revealed that about 30% of inhaled TPM from cigarettes spiked with 14 C-dotriacontane-16,17 was deposited in the lungs of two (sacrificed) dogs.…”
Section: Smoke Generation and Exposure In Inhalation Studies With Nonmentioning
confidence: 99%
“…Some of the more complete studies used radiolabelled markers such as 14 C-dotriacontane, providing de nitive data on the amounts of smoke deposited in the lungs of the experimental animals (13,28).…”
Section: Animal Speciesmentioning
confidence: 99%